2020
DOI: 10.1097/meg.0000000000001696
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 2 binding protein 3 expression on endoscopic ultrasound guided fine needle aspiration specimens in pancreatic ductal adenocarcinoma

Abstract: Background: Despite numerous investigations, we still do not have a specific marker for pancreatic ductal adenocarcinoma. Only guideline-recommended biomarker for pancreatic ductal adenocarcinoma is the CA19-9, but it is also present in other gastrointestinal diseases. IMP3 is a new potential biomarker that is over-expressed in some cancers. The aims of our study were (1) to assess IMP3 in benign pancreatic lesions and pancreatic cancer, and (2) to estimate its concentrations in localized and advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…To overcome problems related to misdiagnosis, several immunohistochemical antibodies have been evaluated; several reports have interpreted the diagnostic value of Maspin, IMP3, S100A, and S100P in the differential diagnosis of PDAC from normal/reactive pancreatic tissue. [15][16][17][18][19][20][21] By contrast, only few studies have evaluated TFFs proteins expression on FNAB. 11 Maspin is an epithelial-specific tumor suppressor gene, whose expression is commonly downregulated in invasive high-grade cancers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To overcome problems related to misdiagnosis, several immunohistochemical antibodies have been evaluated; several reports have interpreted the diagnostic value of Maspin, IMP3, S100A, and S100P in the differential diagnosis of PDAC from normal/reactive pancreatic tissue. [15][16][17][18][19][20][21] By contrast, only few studies have evaluated TFFs proteins expression on FNAB. 11 Maspin is an epithelial-specific tumor suppressor gene, whose expression is commonly downregulated in invasive high-grade cancers.…”
Section: Discussionmentioning
confidence: 99%
“…19 A re-expression of IMP3 has been observed in a series of human malignancies, including PDAC. 19 Most studies showed that IMP3 expression is not tumor specific, although it is a good marker of malignancy. 19 The S100 protein belongs to a family of calcium binding proteins with 25 known members, all of which have a high degree of sequence and structural similarity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with cytohistology alone, cytohistological analysis combined with IMP3 staining had substantially higher diagnostic sensitivity, specificity, and accuracy in endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) samples 85 . Tadic et al and Mikata et al also confirmed these findings 90,91 …”
Section: M6a Modification and Diagnosis Of Pcmentioning
confidence: 92%